Libraries in changed information space - Lasić-Lazić, Jadranka; Banek Zorica, Mihaela; Špiranec, Sonja (2011)
Purpose – This paper seeks to discuss the need for development and conceptualization of the learning outcomes and competences approach in creating information science curricula. Design/methodology/approach – An analytical approach to the theoretical insights and the results of previous and current empirical research projects was taken together with the detailed analysis of the Department of Information Sciences, Faculty of Humanities and Social Sciences, University of Zagreb program in order to prove the necessity of the educational approach based on competences and learning outcomes. Findings – Learning outcomes should be the ultimate goal to be achieved by the teaching staff and students through the educational process. It is necessary that the learning outcomes approach along with the necessity for specific outcomes and competences should be determined by the university teachers on a conceptual as well as an implemental level. Competences that information sciences students are expected to attain (defined by the criterion of employability) have been determined in a way which should facilitate their later employment and enable them to compete in the labour market. At the same time, this kind of approach contributes to the preservation as well as to the prestige of the profession/discipline. Originality/value – The paper presents a new approach to LIS curriculum through defining a framework of competencies based on learning outcomes.
Projekt MZOS
ENG